Opposing Changes in Synaptic and Extrasynaptic N-Methyl-D-Aspartate Receptor Function in Response to Acute and Chronic Restraint Stress - Tse, Yiu Chung; Nath, Moushumi; Larosa, Amanda; Wong, Tak Pan (Frontiers in Molecular Neuroscience, 2021)
A pertinent mechanism by which stress impacts learning and memory is through stress-induced plastic changes in glutamatergic transmission in the hippocampus. For instance, acute stress has been shown to alter the expression, binding, and function of the ionotropic glutamate N-methyl-D-aspartate receptor (NMDAR). However, the consequences of chronic stress, which could lead to various stress-related brain disorders, on NMDAR function remain unclear. While most studies on NMDARs focused on these receptors in synapses (synaptic NMDARs or sNMDARs), emerging findings have revealed functional roles of NMDARs outside synapses (extrasynaptic NMDARs or exNMDARs) that are distinct from those of sNMDARs. Using a restraint stress paradigm in adult rats, the objective of the current study is to examine whether sNMDARs and exNMDARs in the hippocampus are differentially regulated by acute and chronic stress. We examined sNMDAR and exNMDAR function in dorsal CA1 hippocampal neurons from brain slices of adult rats that were acutely (1 episode) or chronically (21 daily episodes) stressed by restraint (30 minutes). We found that acute stress increases sNMDAR but suppresses exNMDAR function. Surprisingly, we only observed a reduction in exNMDAR function after chronic stress. Taken together, our findings suggest that sNMDARs and exNMDARs may be differentially regulated by acute and chronic stress. Most importantly, the observed suppression in exNMDAR function by both acute and chronic stress implies crucial but overlooked roles of hippocampal exNMDARs in stress-related disorders.